Inhibition of NEDD8 and FAT10 ligase activities through the degrading enzyme NEDD8 ultimate buster 1: A potential anticancer approach - Tan, KL; Pezzella, F (Spandidos Publ Ltd, 2024)
Indexed by WOS/ Scopus